Estimation of carbon pool in soil, above and below ground vegetation at different types of mangrove forests in Peninsular Malaysia - Rozainah, Mohamad Zakaria; Nazri, M.N.; Sofawi, Ahmad Bakrin; Hemati, Zhila; Juliana, W.A. (Elsevier, 2018)
This paper evaluated the total carbon stock of mangrove ecosystems in two contrasting sites: a fishing village in Delta Kelantan (DK) and Ramsar sites in Johor Park (JP). In both sites, aboveground carbon was significantly higher than belowground carbon, and stems contained more carbon than leaf and root partitions. The average carbon concentration of individual mangrove species (44.9–48.1%) was not significantly different but the larger biomass of the DK samples resulted in vegetation carbon stock that was higher than that in JP. Season played an important role in soil carbon stock—a pronounced wet season in DK coincided with the dry season in JP. The total carbon pool was estimated to be 427.88 t ha−1 in JP and 512.51 t ha−1 in DK, where at least 80% was contributed by soil carbon. The carbon dioxide equivalent was 1570.32 t ha−1 CO2e (JP) and 1880.91 t ha−1 CO2e (DK).